Well-being balance and lived experiences: understanding the impact of life situations on human flourishing - Brydges, Christopher R.; Thérond, Alexandra; Norris, Troy W. (Frontiers in Psychiatry, 2025)
BackgroundThis study aimed to determine the most significant indicators of positive well-being and understand differences in sources of well-being across different life situations, age groups, genders, and income levels, utilizing a novel measure of positive well-being, the Well-being Balance and Lived Experiences (WBAL) Assessment, which evaluates the frequency of various positive experiences and feelings across a range of activation and arousal levels that have previously been demonstrated to affect subjective well-being and human flourishing.MethodsA sample of 496 evaluable subjects aged 20-69 and census-balanced for gender were recruited from a U.S. population panel. Differences in well-being and sources of well-being were analyzed across subgroups via MANOVA analysis followed by post-hoc ANOVA and Tukey’s HSD analyses using Cohen’s d to determine size and direction of effects between categorical subgroups.ResultsLife situations, including relationship, parenting and employment status, were shown to have a more significant effect on overall well-being than the demographic variables of age, gender and household income. Reported well-being improved significantly with life situations, including companionate relationships (d=0.38, p<0.001) and parenting (d=0.35, p<0.001), that provide greater opportunities for more frequent social connection (d’s=0.25, p<0.01 to 0.62, p<0.001) and purposeful contribution to others’ well-being (d’s=0.34 to 0.71, p<0.001), associated with increased feelings of significance (d’s=0.40 to 0.45, p<0.001) and efficacy (d’s=0.37 to 0.44, p<0.001). An age-related positivity effect was observed, with older adults reporting more frequent positive feelings than younger age groups (d=0.31, p<0.01). Measures of mindset positivity, variety of positive experiences and feelings, and frequency and range of positive feelings across arousal levels each corresponded closely with overall well-being.ConclusionLife situations, including relationship, parenting and employment status, had a more broad and significant effect on wellbeing than age, gender or income. Across life situations, purposeful contribution and social connection, with associated feelings of efficacy and significance were key drivers of differences in well-being. Mindset positivity and variety of positive experiences and feelings correspond closely with overall well-being. Findings from this study can help guide the design and implementation of intervention programs to improve well-being for individuals and targeted subgroups, demonstrating the utility of the WBAL Assessment to evaluate discrete modifiable sources of positive well-being.